Final Bid Price Estimation for Negotiated Contracts: Bargaining Game Theory Approach - El Mahallaoui, Amr (AUC Knowledge Fountain, 2022)
The wide use of the low bid method by employers for awarding construction contracts has created an aggressively competitive environment among contractors in the construction industry. As a result, a contractor may resort to use a low mark-up percentage for his bid to increase his chances of winning, which may lead to losses and conflicts in case he is awarded the project. Additionally, a contractor who reaches the final negotiations stage for a certain project is faced by the dilemma of the minimum discount percentage he may need to offer to the employer that maximizes his chance to win the project. This research presents the framework for a decision support tool / model that uses bargaining game theory to help contractors make rational decisions regarding the discount percentage to offer to the employer during negotiations in order to establish a win-win scenario in which the employer gets the lowest possible price for his project and at the same time the contractor’s profit is maximized. The developed Monte Carlo simulation based python model uses the source code of Gambit in order to determine the Nash Equilibrium of a typical negotiation process in private sector projects; where negotiations are allowed, contractors are procured through competitive bidding, and the low bid method is used for awarding the contracts. The negotiation process is depicted by a game composed of three players (two contractors and one employer), through a two stage negotiation process. Moreover, a real case study of a hospital mega project in Egypt is used to validate the developed python model. The analysis of this case study showed that using the developed model by the winning contractor could have saved him almost 299.5 M EGP of unnecessary discount offered to the employer. Additionally, another objective of this research is to determine and rank the factors that affect the level of aggression (bargaining power) of the two negotiating parties (employer/contractor) in the Egyptian market.